Elijah of Buxton - Curtis, Christopher Paul (New York : Scholastic Press, 2007)
In 1859, eleven-year-old Elijah Freeman, the first free-born child in Buxton, Canada, which is a haven for slaves fleeing the American south, uses his wits and skills to try to bring to justice the lying preacher who has stolen money that was to be used to buy a family's freedom.
Accelerated Reader AR
Keywords: Liberty -- Fiction; Slavery -- Fiction; Blacks -- Fiction -- Canada; North Buxton (Ont.) -- Fiction; Canada -- Fiction